2018
DOI: 10.1090/proc/13970
|View full text |Cite
|
Sign up to set email alerts
|

Restricting irreducible characters to Sylow 𝑝-subgroups

Abstract: We restrict irreducible characters of finite groups of degree divisible by p p to their Sylow p p -subgroups and study the number of linear constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…The operator Ω q was first defined in [5,Section 3] and it is recalled below for the convenience of the reader. Given compositions µ and ν, we denote by µ the unique partition obtained by reordering the parts of µ, and by µ • ν the composition of |µ| + |ν| obtained by concatenating µ and ν.…”
Section: The Proof Of Proposition 38mentioning
confidence: 99%
“…The operator Ω q was first defined in [5,Section 3] and it is recalled below for the convenience of the reader. Given compositions µ and ν, we denote by µ the unique partition obtained by reordering the parts of µ, and by µ • ν the composition of |µ| + |ν| obtained by concatenating µ and ν.…”
Section: The Proof Of Proposition 38mentioning
confidence: 99%
“…The above statement has been verified for various classes of groups in [3]. In particular, when G is the symmetric group S n it is shown that the restriction to a Sylow p-subgroup of any irreducible character of degree divisible by p has at least p distinct linear constituents.…”
Section: Introductionmentioning
confidence: 78%
“…In the second case we can write again δ(γ n ) = φ(γ n−1 )ψ(σ) = 0, by induction. If g = ω n then the result follows from [3,Lemma 3.11].…”
Section: The Proof Of Theorem Amentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, all irreducible characters θ ∈ Irr(P ) appear as constituents of χ P with multiplicity at least θ(1) in this case. In [7,8,9], Giannelli and Navarro investigated a more general situation where χ(1) is divisible by p and χ P has at least one linear constituent λ ∈ Irr(P ). They conjectured (and proved in many cases) that χ P has at least p distinct linear constituents.…”
Section: Introductionmentioning
confidence: 99%